Disgust trait modulates frontal-posterior coupling as a function of disgust domain - Borg, Charmaine (Oxford University Press, 2013)
Following the two-stage model of disgust, ‘core disgust’ (e.g. elicited by rotten food) is extended to stimuli that remind us of our animal nature ‘AR disgust’ (e.g. mutilations, animalistic instincts). There is ample evidence that core and AR represent distinct domains of disgust elicitors. Moreover, people show large differences in their tendency to respond with disgust to potential disgust elicitors (propensity), as well as in their appraisal of experiencing disgust (sensitivity). Thus these traits may be important moderators of people's response patterns. Here, we aimed to find brain mechanisms associated with these distinct disgust domains and traits, as well as the interaction between them. The right ventrolateral occipitotemporal cortex, which preferentially responded to visual AR, was functionally coupled to the middle cingulate cortex (MCC), thalamus and prefrontal cortex (medial, dorsolateral), as a function of disgust domain. Coupling with the anterior part of MCC was modulated by disgust ‘propensity’, which was strongest during AR. Coupling with anterior insula and ventral premotor cortex was weaker, but relied fully on this domain–trait interaction. Disgust ‘sensitivity’ modulated left anterior insula activity irrespective of domain, and did not affect functional connectivity. Thus a frontal-posterior network that interacts with disgust ‘propensity’ dissects AR and core disgust.